Long-term response with everolimus for metastatic renal cell carcinoma refractory to sunitinib - Molina, Ana M. (Springer US, 2010)
A 70-year-old man with metastatic renal cell carcinoma developed progressive liver metastases after 8 weeks of treatment with the multitargeted tyrosine kinase inhibitor (TKI) sunitinib. He then participated in the phase III placebo-controlled clinical trial of the oral mammalian target of rapamycin (mTOR) inhibitor everolimus, initially randomized to placebo (but had disease progression after 3 months) and crossed over to everolimus at time of unblinding. The patient had stable disease after 8 weeks (two cycles) of everolimus that was maintained until 28 months of therapy, at which time the patient had achieved a partial response. This case illustrates the potential for patients with metastatic renal cell carcinoma, a malignancy with historically poor prognosis, to derive long-term benefit from everolimus when used in a manner consistent with its approved indication (after TKI therapy with sunitinib or sorafenib).